Narrow-Linewidth Tunable Fiber Laser Based on Laser-Induced Graphene Heated Fiber Bragg Grating with Low Voltage - Baoshan Gu; Feng Yang; Li Shen; Shouhuan Zhou; Shutong Wang; Sha Wang (Photonics, 2023)
In this paper, we demonstrate a narrow-linewidth tunable fiber laser based on laser-induced graphene (LIG) paper-heated fiber Bragg grating (FBG) with low voltage. A linewidth of less than 600 Hz is achieved by the combination of a piece of unpumped Er-doped fiber and an FBG. Changing the temperature of the FBG will result in the central transmission spectrum shifting, and hence the laser wavelength tuning. LIG-heated (LIG-H) fabrication on polyimide (PI) paper by CO2 laser is used to offer temperature control of the FBG. By adjusting the voltage of the LIG-H from 0 to 5 V, the temperature of the LIG-H can be changed from room temperature up to 220 °C, while the central wavelength of the output laser can be continuously adjusted from 1549.5 nm to 1552 nm with a full range of 2.5 nm. The proposed technique by electric control of LIG-H can provide a low-cost and compact wavelength tunable laser design.